2014
DOI: 10.1371/journal.pone.0101931
|View full text |Cite
|
Sign up to set email alerts
|

Neuropilin-1 Promotes Epithelial-to-Mesenchymal Transition by Stimulating Nuclear Factor-Kappa B and Is Associated with Poor Prognosis in Human Oral Squamous Cell Carcinoma

Abstract: BackgroundThe epithelial-to-mesenchymal transition (EMT) is a key process in carcinogenesis, invasion, and metastasis of oral squamous cell carcinoma (OSCC). In our previous studies, we found that neuropilin-1 (NRP1) is overexpressed in tongue squamous cell carcinoma and that this overexpression is associated with cell migration and invasion. Nuclear factor-kappa B (NF-κB) plays an essential role both in the induction and the maintenance of EMT and tumor metastasis. Therefore, we hypothesized that NRP1 induces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
60
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(66 citation statements)
references
References 44 publications
3
60
0
1
Order By: Relevance
“…Studies have suggested that overexpressed NRP-1 can induce EMT in oral squamous cell carcinoma cells and human gastric cancer cells [10,24] . Three signaling pathways are involved in EMT induced by NRP-1: TGF-induce EMT in oral scMet.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have suggested that overexpressed NRP-1 can induce EMT in oral squamous cell carcinoma cells and human gastric cancer cells [10,24] . Three signaling pathways are involved in EMT induced by NRP-1: TGF-induce EMT in oral scMet.…”
Section: Discussionmentioning
confidence: 99%
“…NRP-1, initially discovered in the developing nerve fiber axons, is a receptor of semaphorin 3A and vascular endothelial growth factor (VEGF)-165 and is mainly expressed in glomerular epithelial cells and collecting ducts [9] . Studies have suggested that NRP-1 can induce EMT in tumor cells [10] , and its expression is increased in hepatic fibrosis [11,12] . Considering the importance of PAX2-induced EMT in renal tubular epithelial cells and its relationship with NRP-1, we selected NRP-1 as a candidate target gene and we hypothesized that PAX2 regulates NRP-1 expression in renal tubular epithelial cells, and that NRP-1 is involved in RIF.…”
Section: Introductionmentioning
confidence: 99%
“…Oral squamous cell carcinoma is the most frequently occurring malignant oral tumor in the oral cancer group (2); however, to the best of our knowledge, the effectiveness of VPA on OSCC has not been widely investigated. In the present study, the effects of VPA on OSCC were examined in vivo and in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…OSCC is a complex disease associated with numerous changes in genetic and epigenetic interactions; however, the mechanisms remain poorly understood (2). Alterations in the histone acetylation/deacetylation balance, have been suggested to underpin the altered gene expression patterns detected in various pathological conditions, including cancer (3) and cardiac hypertrophy (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…A recent report showed that high Notch1 expression is associated with low survival rate in esophageal squamous cell cancer (10). Furthermore, Chu et al (11) reported that nuclear factorkappa B also influences the prognosis of oral squamous cell carcinoma. In addition, Wnt5a positivity was reported as a sign of short survival period in NSCLC (12).…”
Section: Introductionmentioning
confidence: 99%